Perancangan Sistem Layanan Dokumen Kependudukan Berbasis Web Studi Kasus Desa Neglasari Bogor - Sismadi, Sismadi (LPPM Universitas Bina Sarana Informatika, 2021)
Excellent and efficient service and right on target is a priority that is expected by every agency, both government and private institutions. Neglasari village is one of the government agencies directly related to population administrative services. These services include, among others, birth registration, death certificates, and population transfers. The service at the Neglasari village office still uses paper as a recording tool. With this condition, errors (human error) often occur archive accumulation and loss or damage to resident archives. To anticipate these problems, a digital-based data processing system is needed. The system is built with a prototype and web-based model so that administrative services for residents are direct users who can interact with the system in real-time so that the chance of error is minimal. Another benefit of this system is that it is hoped that there will be no queues and long waiting times in managing administrative documents, besides that the efficiency and effectiveness of village staff performance will be better..